PROSES KOGNITIF SISWA FIELD INDEPENDENT DAN FIELD DEPENDENT DALAM MENYELESAIKAN MASALAH MATEMATIKA - Buaddin Hasan (IKIP Siliwangi, 2020)
Cognitive process is a person's mindset in accepting, processing and representing the knowledge given by six agreed aspects; remember, understand, apply, analyze, evaluate and create. This research studies to describe the cognitive processes of students with independent and cognitive fields of cognitive style in solving mathematical problems. The subject of this study was one student with field independent and field dependent cognitive styles. The instrument used was the GEFT test, problem understanding test, and interview guidelines. The process of data analysis is done by triangulating data, presenting data and drawing conclusions. From the research results obtained by students with field independent cognitive style has more detailed characteristics in making explanations and being able to organize the information obtained and be able to save themselves from the development of the adjacent environment. Students with dependent cognitive styles tend to be only able to accept given concepts and are more global in providing explanations about the difficulties in the concept, besides students with dependent cognitive style are still needed by the surrounding environment.Cognitive process is a person's mindset in accepting, processing and representing the knowledge given by six agreed aspects; remember, understand, apply, analyze, evaluate and create. This research studies to describe the cognitive processes of students with independent and cognitive fields of cognitive style in solving mathematical problems. The subject of this study was one student with field independent and field dependent cognitive styles. The instrument used was the GEFT test, problem understanding test, and interview guidelines. The process of data analysis is done by triangulating data, presenting data and drawing conclusions. From the research results obtained by students with field independent cognitive style has more detailed characteristics in making explanations and being able to organize the information obtained and be able to save themselves from the development of the adjacent environment. Students with dependent cognitive styles tend to be only able to accept given concepts and are more global in providing explanations about the difficulties in the concept, besides students with dependent cognitive style are still needed by the surrounding environment.